Intratumoral microbiota: implications for cancer progression and treatment - Xie, Zehang; Wu, Zhenguo; Liu, Yan; Gu, Yu; Niu, Jiahao; Lv, Kun (Frontiers in Microbiology, 2025)
The human body has a diverse range of microbiota that influences human physiological processes and alters disease risk, involving cancer. Metagenomic sequencing investigations have revealed that the microbiota is an element of the tumor microenvironment, affecting tumor proliferation and responsiveness to current anticancer treatments. The notion of intratumoral microbiota was subsequently introduced. Intratumoral microorganisms have been identified in kinds of cancer, including pancreatic, colorectal, liver, esophageal, breast, and lung malignancies. Microbiota may inhabit tumor tissues by mucosal breakdown, neighboring tissue migration, and hematogenous spread, influencing the biological behavior of tumors as a significant component of tumor’s microenvironment. The intratumoral microbiota may facilitate the onset and progression of malignancies through DNA mutations, activation of carcinogenic pathways, alteration of anticancer medication metabolism, and commencement of metastasis. This document is to present an overview of intratumoral microbiota, their prevalence and progression in cancer, their detection and therapy, and to evaluate the potential and limitations of research in this domain. We intend to generate ideas for investigating intratumoral microbiota as possible treatment targets and biomarkers for tumor assessment, prognosis, and detection.